Copper‐mediated polyurethane materials with enzyme‐like catalysis for biocompatibility improvement in blood environments. Issue 1 (24th May 2021) - Dou, Jiaxin; Li, Peichuang; Zhao, Yuancong; Zhou, Lei; Li, Xin; Wang, Jin; Huang, Nan
Abstract: Because of their good performance, including biocompatibility and mechanical properties, polyurethanes (PUs) are widely used in medical devices. However, undesired compatibility troubles, including thrombus, inflammation, and hyperplasia, still limit the applications of PUs. In this study, copper‐mediated polyurethane (PU‐Cu) materials with enzyme‐like catalysis were prepared. The PU‐Cu materials effectively catalysed the nitric oxide (NO) released from endogenous NO donors because of the glutathione peroxidase (GPx)‐like function of copper ion. The PU‐Cu materials were respectively evaluated via platelet adhesion and endothelial cell (EC), smooth muscle cell (SMC), and macrophage (MA) cultures. Scanning electron microscopy results showed that PU‐Cu materials significantly inhibited platelet adhesion and activation. Meanwhile, PU‐Cu materials not only promote the proliferation of EC but also inhibit SMC growth. Moreover, MA culture results intuitively stated the anti‐inflammatory ability of PU‐Cu. In addition, experimental samples were implanted into the subcutaneous tissue of Sprague Dawley rats. The anti‐inflammatory function of PU‐Cu was further confirmed by haematoxylin‐eosin staining results. With regard to their excellent biological performance, PU‐Cu materials are proposed for biocompatibility improvement of blood‐contacting materials, which should in turn provide new ideas for advanced medical devices.